Gamma rays from clumpy wind-jet interactions in high-mass microquasars - Cita, V. M. de la (2017)
Context. The stellar winds of the massive stars in high-mass microquasars are thought to be inhomogeneous. The interaction of these inhomogeneities, or clumps, with the jets of these objects may be a major factor in gamma-ray production. Aims. Our goal is to characterize a typical scenario of clump-jet interaction, and calculate the contribution of these interactions to the gamma-ray emission from these systems. Methods. We use axisymmetric, relativistic hydrodynamical simulations to model the emitting flow in a typical clump-jet interaction. Using the simulation results we perform a numerical calculation of the high-energy emission from one of these interactions. The radiative calculations are performed for relativistic electrons locally accelerated at the jet shock, and the synchrotron and inverse Compton radiation spectra are computed for different stages of the shocked clump evolution. We also explore different parameter values, such as viewing angle and magnetic field strength. The results derived from one clump-jet interaction are generalized phenomenologically to multiple interactions under different wind models, estimating the clump-jet interaction rates, and the resulting luminosities in the GeV range. Results. If particles are efficiently accelerated in clump-jet interactions, the apparent gamma-ray luminosity through inverse Compton scattering with the stellar photons can be significant even for rather strong magnetic fields and thus efficient synchrotron cooling. Moreover, despite the standing nature or slow motion of the jet shocks for most of the interaction stage, Doppler boosting in the postshock flow is relevant even for mildly relativistic jets. Conclusions. For clump-to-average wind density contrasts greater than or equal to ten, clump-jet interactions could be bright enough to match the observed GeV luminosity in Cyg X-1 and Cyg X-3 when a jet is present in these sources, with required non-thermal-to-total available power fractions greater than 0.01 and 0.1, respectively.